Alismatis Rhizoma methanolic extract—Effects on metabolic syndrome and mechanisms of triterpenoids using a metabolomic and lipidomic approach - Jia, Li; Zhang, Min; Wang, Pengli; Wang, Liming; Lei, Peng; Du, Ruijiao; Han, Lifeng; Zhang, Peng; Wang, Yuefei; Jiang, Miaomiao (Frontiers in Pharmacology, 2022)
Alismatis rhizoma is a traditional Chinese medicine. Studies have demonstrated that Alismatis rhizoma also had therapeutic effects on metabolic syndrome. However, the pharmacodynamic material basis and mechanism are still unclear. First, UHPLC/Q-Orbitrap MS was used to conduct the chemical components of Alismatis rhizoma extract, and 31 triterpenoids and 2 sesquiterpenes were preliminarily identified. Then, to investigate the mechanism of Alismatis rhizoma extract on metabolic syndrome by establishing a mouse model of metabolic syndrome induced by high-fructose drinks. The results of serum biochemical analysis showed that the levels of TG, TC, LDL-C, and UA after the Alismatis rhizome extract treatment were markedly decreased. 1H NMR was used to conduct non-targeted metabolomics studies. A total of 20 differential metabolites are associated with high fructose-induced metabolic syndrome, which is mainly correlated to the 11 metabolic pathways. Moreover, UHPLC/Q-Orbitrap MS lipidomics analysis found that a total of 53 differential lipids were screened out. The results showed that Alismatis rhizoma extract is mainly reducing the synthesis of glycerophospholipid and ceramide and improving the secretion of bile acid. This study shows that Alismatis rhizoma extracted can treat metabolic syndrome mainly by inhibiting energy metabolism, amino acid metabolism, and regulating bile acid to reduce phospholipid content.